Impact of fractional CO2 laser treatment on hypertrophic scars and keloids: a systematic review - Luciana El Halal Schuch; Alessandra Haddad; Miguel Francischelli; Isabel Crivelatti (Revista Brasileira de Cirurgia Plástica)
Introduction: Hypertrophic scars and keloids cause aesthetic and functional damages, and are difficult to treat. This review aimed to identify prospective studies on fractional CO2 laser to present the clinical and histological changes and the methodology used for the evaluation of scars before and after intervention. Methods: We conducted an electronic review (LILACS, Medline, and SciELO) of studies published between January 2004 and December 2017, using the search terms "keloid/queloide," "hypertrophic scar/cicatriz hipertrófica," and "CO2 laser ," according to the PRISMA Statement. Studies that compared scars before and after isolated treatment with fractional CO2 laser were selected. Two independent reviewers analyzed the data. Results: One hundred two articles were analyzed, of which 7 met the inclusion criteria. Of the 7 articles, all analyzed hypertrophic scars, 2 analyzed keloids in addition to hypertrophic scars, and 3 analyzed histological changes. Most studies showed a statistically significant difference in clinical scores between before and after treatment of hypertrophic scars, with improvement in symptoms, flexibility, and scar height. Between the 2 studies that analyzed keloids, 1 reported a clinical difference after treatment. The histological changes showed significant differences in the orientation and density of the collagen fibers, and in the thickness of the epidermis. Conclusion: The use of fractional CO2 laser should be considered as a promising treatment option for pathological scars, as it improves clinical signs and symptoms such as color, thickness, and pruritus.